Atom-Probe Tomographic Analyses of Hydrogen Interstitial Atoms in Ultrahigh Purity Niobium. (21st April 2015) - Kim, Yoon-Jun; Seidman, David N.
Abstract: Atomic-scale characterization of hydrogen and formation of niobium hydrides, using ultraviolet (wavelength=355 nm) picosecond laser-assisted local-electrode atom-probe tomography, was performed for ultrahigh purity niobium utilizing different laser pulse energies, 10 or 50 pJ/pulse or voltage pulsing. At 50 pJ/pulse, hydrogen atoms migrate onto the 110 and 111 poles as a result of stimulated surface diffusion, whereas they are immobile for <10 pJ/pulse or for voltage pulsing. Accordingly, the highest concentrations of H and NbH were obtained at 50 pJ/pulse. This is attributed to the thermal energy of the laser pulses being transferred to pure niobium specimens. Therefore, we examined the effects of the laser pulse energy being increased systematically from 1 to 20 pJ/pulse and then decreasing it from 20 to 1 pJ/pulse. The concentrations of H, H2, and NbH and the atomic concentration ratios H2 /H, NbH/Nb, and Nb 3+ /Nb 2+ were calculated with respect to the systematically changing laser pulse energies. The atomic concentration ratios H2 /H and NbH/Nb are greater when decreasing the laser pulse energy than when increasing it, because the higher residual thermal energy after decreasing the laser pulse energy increases the mobility of H atoms by supplying sufficient thermal energy to form H2 or NbH.